Do Poor Countries Really Need More IT? : The Role of Relative Prices and Industrial Composition - Eden, Maya; Gaggl, Paul (World Bank, Washington, DC, 2015)
Conventional wisdom suggests too little information and communication technologies (ICT) in poor countries. Indeed, within 70 countries at various levels of development, there is a positive relationship between income per capita and the capital share of ICT. While this regularity is consistent with explanations based on technology adoption lags and ICT-labor substitutability, there is little empirical support for these hypotheses. Instead, the paper establishes that this regularity can be fully accounted for by (a) relatively higher ICT prices in low-income countries and (b) industrial composition.